INCREASING THE BUSINESS SCALE OF BUMDES CIPTAGUMATI THROUGH DIGITALIZATION OF ACCOUNTING AND MARKETING - Kanti, Runita Arum; Fatmawati, Faoziah Ulfah; Yuliafitri, Indri (LPPM Univ. Ibn Khaldun Bogor, 2024)
Digitalization of marketing and accounting is a major development in today's business world. With the advancement of technology, many businesses have begun to adopt new ways of marketing and managing finances. Digitalization helps a system become more efficient and effective in marketing products/services and managing finances. Therefore, digital transformation is very much needed to be implemented so that all levels of society can utilize it optimally. In reality, there are still many small businesses that do not understand the importance of developing its business units through digitalizing marketing, and digitalizing financial processes. A Community Service Program with the theme